Pre-covid19: Knowledge and Level of Vaccine Acceptance among University Students - Chee Wai Yip; Ain Nor Aliya Zulhelmi Zulhelmi; Muhammad Iqbal Abu Latiffi; Nazlina Ibrahim; Mohamad Rahim Kamaluddin; Jaya Kumar Murthy; Muhammad Arif Yahya; Maryam Azlan; Nur Kareelawati Abd. Karim; Herryawan Ryadi Eziwar Diyari; Mohd Hanafy Gausmian; Mohd Ridzwan Yaakub; et al. (The Malaysian Society of Applied Biology, 2025)
Index by MyCite